2011 International Conference on Advanced Power System Automation and Protection 2011
DOI: 10.1109/apap.2011.6180647
|View full text |Cite
|
Sign up to set email alerts
|

Short-term wind power prediction based on combined grey-Markov model

Abstract: The rapid growth of wind generation is introducing additional variability and uncertainty into power system operations and planning. Wind power forecasting will improve the wind power integration in both economic and technical aspects. In the paper, a combined approach based on grey model and Markov model was proposed to predict wind power in a short term. Firstly a Grey model was created to forecast the wind speed. Secondly the residual error which was obtained by subtracting the predicted values from actual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In this methodology, the data present in the system error is extracted to ensure greater accuracy of forecasting. To establish enhanced accuracy of the forecast, a combined grey and Markov model is implemented to ensure greater precision [118], [119]. In this combined methodology, the errors forecasted by the grey model are categorized into different conditions using the Markov model and for each conditions the probability is estimated.…”
Section: Review Of Various Machine Learning Methods For Wind Forecastmentioning
confidence: 99%
“…In this methodology, the data present in the system error is extracted to ensure greater accuracy of forecasting. To establish enhanced accuracy of the forecast, a combined grey and Markov model is implemented to ensure greater precision [118], [119]. In this combined methodology, the errors forecasted by the grey model are categorized into different conditions using the Markov model and for each conditions the probability is estimated.…”
Section: Review Of Various Machine Learning Methods For Wind Forecastmentioning
confidence: 99%
“…The Grey Model GM(1,1) : The GM (1,1) is the most used in prediction systems [11]. The GM(1,1) modelling process :…”
Section: Machine Learning and Grey Model Descriptionmentioning
confidence: 99%
“…Thus, the common way for high accuracy is to increase the complexity of the model. With the continuous development of artificial intelligence technology, wind power prediction based on machine learning [5][6][7][8] and deep learning [9][10][11][12][13] has become a hot topic, compared to the traditional physical and statistical methods, and the prediction accuracy has been greatly improved. Due to the complexity of the structures, the models have the ability to process a large number of data and to better reflect the non-linear and non-stationary nature of wind power.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity of the structures, the models have the ability to process a large number of data and to better reflect the non-linear and non-stationary nature of wind power. The work in Reference [5] used the Markov model divided residual error into several different states, the residual values were further forecasted through calculating the probability distribution of each state, the residual errors were used to correct the predicted values to improve the accuracy of wind speeds, and the results showed that the Markov model can improve the short-term forecasting accuracy of wind power effectively. The work in Reference [6] used the K-nearest neighbor (KNN) algorithm to select historical wind speed points and built an SVR model to obtain the fusion wind speed, which improves the accuracy of the wind speed prediction.…”
Section: Introductionmentioning
confidence: 99%